Selenium and its compounds in aquatic plant Veronica anagallis-aquatica. (May 2016) - Kroflič, Ana; Germ, Mateja; Mechora, Špela; Stibilj, Vekoslava
Abstract: The uptake, distribution and determination of Se and its compounds in macrophyte Veronica anagallis-aquatica were investigated. V. anagallis-aquatica and sediments were sampled in years 2009–2011 and in 2013 in three Slovenian watercourses flowing through an agricultural area, where addition of Se in feedstuffs has been performed for about 25 years. Se content in sediments were up to 0.86 μg g −1 and in whole plant varied from 0.186 to 1.535 μg g −1, all on dry weight basis. Se content were measured also in different plant parts; highest content were found in roots and lowest in stems. Separation of extractable Se compounds was performed by ion exchange chromatography and for on-line detection inductively coupled plasma-mass spectrometry was used. The results showed that only approximately 24% of Se in the macrophyte was extracted using enzyme Protease XIV. Extractable Se in plant parts varied from 10.5% in roots to 29.6% in leaves. Identification of Se(IV) and Se(VI) was achieved but no Se-amino acids were detected even at highest Se content. According to our results, we assume that 25 years of Se addition in feedstuff shows minimal impact on Se content in the selected agricultural area. Highlights: Se in feedstuffs did not effect to Se content in selected agricultural area. Se and its compounds were investigated in macrophyte Veronica anagallis-aquatica. Se content in whole plant was up to 1.535 μg g −1 dry weight. In enzymatic plant extract approximately 24% of extractable Se was found. In soluble form, Se(VI) and Se(IV) were found, but no Se-amino acids.